TANGGAP KARAKTER MORFOFISIOLOGI JAGUNG TERHADAP KOMPOS LIMBAH JAGUNG DAN NPK DI TANAH ULTISOL - Yohanes Wahyudi; Iwan Sasli; Radian Radian (Partner, 2021)
Maize (Zea mays L.) is a very sensitive crop plant towards fertilization. Sufficient macro and micronutrients in the soil must be available during the maizes growth phase. Providing nutrients for maizes can be done by adding organic or inorganic fertilizers. The aim of this research is to determine the effects of interactions from maize waste composts and NPK fertilizers on the morphophysiological characters of maizes in ultisol soil. The research method used was a Randomized Block Design (RBD) with 2 factorials, the dose of maize waste composts (K) and the dose of NPK fertilizers (P). The result showed that the factor K treatment is significantly affected the growth and the yield components of maizes. The level k2 treatment (20 tons ha-1 of maize waste composts) generally gave the highest mean for maize cobs length and diameter, seeds per maize cob and per plot. Key Words: yield, maize, compost, morphophysiology, ultisol.